Experience with transcatheter closure of secundum atrial septal defects using the Amplatzer septal occluder: a single centre study in 236 consecutive patients. Issue 2 (1st February 2003) - Fischer, G; Stieh, J; Uebing, A; Hoffmann, U; Morf, G; Kramer, H H
Abstract : Aim: To evaluate the safety and efficacy of transcatheter closure of secundum atrial septal defects (ASD) with the Amplatzer septal occluder. Methods: 236 consecutive patients with a significant ASD (age 6 months to 46 years, median 5 years; body weight 6.5–79 kg, median 18 kg) were considered for transcatheter closure with the Amplatzer septal occluder; 18 patients with defects that were too large or with a deficient inferior margin were excluded from attempted transcatheter closure after initial transthoracic (4) or transoesophageal echocardiography (14). Results: At cardiac catheterisation, devices were not implanted in 18 patients because the stretched diameter of the ASD was too large (4), the device was unstable (4), compromised the mitral valve (1), or obstructed the upper right pulmonary vein (1); eight patients with additional systemic or pulmonary vein anomalies (5) or a Qp:Qs less than 1.5 (3) were excluded after angiographic and haemodynamic assessment. Thus ASD closure was done successfully in 200 patients (procedure time 25–210 minutes, median 66 minutes; fluoroscopy time 2.5–60 minutes, median 12 minutes), among whom 22 had multiple ASDs (14) or a septal aneurysm (8). The diameter of the devices ranged between 6–34 mm. Severe procedure related complications (retroperitoneal bleeding, air embolism) occurred in two cases. At follow up (33 days to 4.3 years, median 2.3 years) complete closure was documented in 94%, with a trivial residual shunt in 12 patients. Conclusions: The Amplatzer septal occluder is very efficient and offered interventional ASD closure in 84.7% of our group of consecutive patients, with excellent intermediate results.